1993
DOI: 10.1007/bf00027208
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting in vitro clonal propagation of Prosopis cineraria

Abstract: Genotype, age of tree, nature of explant and size (length and diameter), season of explant collection, explant position on medium, plant growth regulators and certain additives (ascorbic and citric acids, adenine sulphate, L-arginine, glutamine and ammonium citrate), incubation conditions, and subculturing period greatly influenced the in vitro clonal propagation of P. cineraria. The maximum number of lo-12 shoots were induced from the nodal shoot segment from pruned thorny adult trees on Murashige and Skoog's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 20 publications
3
33
1
5
Order By: Relevance
“…The old/perennial shoots of unlopped tree, if cultured, did not respond in vitro. It is suggested that the perennial shoots/tissues experience types of stresses like summer heat, severe winter, and extreme drought during the year, and accumulate anti-metabolic substances like phenols and ABA, which inhibit growth in culture (Shekhawat et al 1993). Pruning/lopping/pollarding of mature tree and elimination/removal of aged tissues resulted in the production of reinvigorated shoots during subsequent spring.…”
Section: Establishment Of Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The old/perennial shoots of unlopped tree, if cultured, did not respond in vitro. It is suggested that the perennial shoots/tissues experience types of stresses like summer heat, severe winter, and extreme drought during the year, and accumulate anti-metabolic substances like phenols and ABA, which inhibit growth in culture (Shekhawat et al 1993). Pruning/lopping/pollarding of mature tree and elimination/removal of aged tissues resulted in the production of reinvigorated shoots during subsequent spring.…”
Section: Establishment Of Culturesmentioning
confidence: 99%
“…The treatment of explants with chilled, sterile antioxidant solution checked excessive phenolic exudation and browning of tissue and cultures (Phulwaria et al 2012a, b). It has been observed in woody plants that antioxidant solutions may promote growth and development of the shoots particularly at the stage of culture establishment (Shekhawat et al 1993;Sanjaya et al 2006;Rai et al 2010). Explants were cultured on 0.8 % agar-gelled MS medium containing BAP or Kn for shoot bud induction.…”
Section: Establishment Of Culturesmentioning
confidence: 99%
“…1d, Table 2). The repeated transferring has been recommended as a method for rejuvenation of mature explants for micro-clonal propagation of several woody plants (Pierik 1990;Shekhawat et al 1993;Phulwaria et al 2011). The increase in shoot number after repeated transfer of mother explants for different passages may be due to suppression of apical dominance during subculture that induced basal dormant meristametic cells to form new shoots (Tripathi and Kumari 2010).…”
Section: Effect Of Plant Growth Regulator On Bud Breakmentioning
confidence: 99%
“…NORTON and NORTON (1985) observed similar genotype dependent variation for shoot proliferation and plant growth regulator requirement amongst 20 cultivars of Family Ericaceae. Intraspecific variations amongst spiny and spineless genotypes of Prosopis cineraria for their shoot forming ability and phytohormone requirements were also registered (KACKAR et al, 1991;SHEKHAWAT et al, 1993). Coppicing ability of clones and their multiple bud induction capacity seems to exhibit a correlation and there by giving impetus to our belief that said traits are genetically controlled.…”
Section: Discussionmentioning
confidence: 97%